Analytic Hierarchy Process (AHP) Method for Determining the Best Employee - Setiawan, Iwan; Wahyudi, Muhammad; Wahyuni, Sri; Cikayanti, Yoyoh (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
The aims of the research is to determining the best employee to increase work motivation. Selection subjectivity is a prevalent issue that might impact employee motivation. For objective assessment, this work intends to create a Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP). The accuracy of the judgment is guaranteed by the test results, which indicate that the Consistency Ratio (CR) and Consistency Index (CI) values are less than 0.1.